Walker. Season three [videorecording (DVD)] - Fahey, Seamus Kevin; Padalecki, Jared, 1982-; Morgan, Lindsey, 1990-; Allen, Keegan, 1989-; Pileggi, Mitch (CW, 2023)
Season Three of WALKER picks up right where season two left off in the sobering aftermath of the question: "Where's dad?" Texas Ranger Cordell Walker has his hands tied literally. Taken and held captive by an anarchist group who is determined to break him, Walker must face a painful memory from his past he's never shared with anyone and team up with an unexpected ally, Julia if he wants to get out alive.